The Effectof Integrated Turkish and Science Activities in Pre-School Education on Children's Environmental Perception - Sak, Semra; Çağlar, Atila; Öztürk, Burcu (Kastamonu Egitim Dergisi, 2024)
Purpose of the Study: The purpose of this study is to determine the effect of integrated Turkish and science activities in the preschool period on children's environmental perception. Materials and Methods: In the qualitative dimension of the mixed method, a phenomenological design was employed, while in the quantitative dimension, a quasi-experimental design was used. Thestudy conductedwith 20 children.In the experimental procedure, children in both the experimental and control groups were asked to draw an environment picture, and one-on-one interviews were conducted with the children regarding their drawings. The drawings were evaluated using DAET-R and were attempted to be transformed into qualitative form with yellow and blue color tones. Findings: In the final tests, experimental groups’ figures increased in the drawings. It was found that the final test drawings of the children in the experimental group were related to the illustrated books used in the integrated activities. Key Points: As a result of the study, it was determined that the change in environmental perception of the children in the experimental group, where integrated Turkish and science activities developed with illustrated children's books were applied, progressed more prominently compared to the children in the control group.
Keywords: 4. Education